Grass 2 Cash @Scale Project overview and theory of change - Sibiko, Kenneth W.; Burkart, Stefan; Notenbaert, An M. O. (2024)
The primary goal of the second phase of the Grass 2 Cash project was to scaleup the use of Brachiaria forage hybrids and cultivars, as well as one Panicum maximum variety among vulnerable and market-oriented farmers in East Arica. Here we provide information about the project and the refined theory of change.